Cannabinoid hyperemesis should be recognised as an effect of chronic cannabis abuse - Ishaq, Sauid (Shaheed Beheshti University of Medical Sciences, 2014)
Here we describe the second reported case of cannabinoid hyperemesis in UK. A 42 years old patient presented on more than one occasion with vomiting, abdominal pain, fever and dehydration and treated as sepsis with antibiotics. Extensive investigations including upper GI endoscopy, colonoscopy, chest X-ray, abdominal ultrasound, abdominal CT scan, barium swallow and echocardiogram; all reported normal. Once the diagnosis of cannabinoid hyperemesis was established, he was advised to abstain from cannabis use resulting in complete resolution of his symptoms.